Operator Theory, Systems Theory and Scattering Theory: Multidimensional Generalizations - Alpay, Daniel.; Alpay, Daniel.; Vinnikov, Victor.; Vinnikov, Victor. (Operator Theory: Advances and Applications,, 2005)
Operator theory, system theory, scattering theory, and the theory of analytic functions of one complex variable are deeply related topics, and the relationships between these theories are well understood. When one leaves the setting of one operator and considers several operators, the situation is much more involved. There is no longer a single underlying theory, but rather different theories, some of them loosely connected and some not connected at all. These various theories, which one could call "multidimensional operator theory", are topics of active and intensive research. The present volume contains a selection of papers in multidimensional operator theory. Topics considered include the non-commutative case, function theory in the polydisk, hyponormal operators, hyperanalytic functions, and holomorphic deformations of linear differential equations. The volume will be of interest to a wide audience of pure and applied mathematicians, electrical engineers and theoretical physicists.